Heterogeneity in Migration Responses to Climate Shocks: Evidence from Madagascar - Francesca Marchetta; David E. Sahn; Luca Tiberti; Johany Dufour (Institute of Labor Economics (IZA), 2021)
We analyze the impact of climate events on migration among a cohort of young adults residing in rural Madagascar. We find a strong negative impact of drought on the decision of youth to migrate in the year after the adverse weather shock. Household assets and access to savings institutions attenuate this impact, consistent with the notion that wealth and savings cushion the blow of the shock on the resources required to finance migration. We also find that households that report more social connections outside their villages are more likely to have their young adult members migrate. Our findings suggest that the liquidity constraints from climate shocks that prevent youth migration are more binding for young women who migrate largely for reasons of marriage and education. Males, in contrast, are more likely to migrate in search of employment, which often has higher economic returns than migration motivated by marriage and education. These factors likely explain why drought deters migration of young women, but not so for young men who still choose to migrate in search of a job.
Keywords: O15; J13; N3; N57; 330; climate shocks; Madagascar; youth migration; internal migration